Dark Temporal Cavity Soliton Pairs in Fabry-Pérot Resonators with Normal Dispersion and Orthogonal Polarizations - Campbell, Graeme N.; Hill, Lewis; Del'Haye, Pascal; Oppo, Gian Luca (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Temporal cavity solitons have attracted significant interest for optical frequency comb generation with a large number of applications including precision spectroscopy, LIDAR, and channel generation for telecom systems [1]. Here we introduce dark and dark-bright vectorial temporal cavity soliton pairs in a Fabry-Pérot (FP) resonator with normal dispersion and two orthogonal polarizations. A FP resonator with highly reflective mirrors, Fig. 1a, which contains a normally dispersive Kerr medium and driven by an input field with two orthogonal polarizations can be modeled [2] with the following system of two integro-partial differential equations (equation presented) where ψ± are the fields of left and right handed circular polarization with input fields S and detuning to the nearest cavity resonance θ. Here t,ζ are the slow time and fast time variables describing the evolution over many round trips and single round trip tR respectively. Integral terms correspond to angled brackets and take the form of global averages in the fast time over a round trip of the resonator. They arise due to the counterpropagation of the fields inherent in a FP configuration or in bidirectionaly pumped ring resonators [3].
CRIS-Team Scopus Importer:2024-12-16